Microbial modulation of the gut microbiome for treating autoimmune diseases. (3rd October 2018) - Balakrishnan, Baskar; Taneja, Veena
ABSTRACT: Introduction : Many studies have shown the relationship between autoimmune diseases and the gut microbiome in humans: those with autoimmune conditions display gut microbiome dysbiosis. The big question that needs to be addressed is if restoring eubiosis of the gut microbiota can help suppress the autoimmune condition by activating various immune regulatory mechanisms. Inducing these self-healing mechanisms should prolong good health in affected individuals. Area covered : Here, we review the available clinical and preclinical studies that have used selective bacteria for modulating gut microbiota for treating autoimmune diseases. The potential bacterial candidates and their mechanism of action in treating autoimmune diseases will be discussed. We searched for genetically modified and potential probiotics for diseases and discuss the most likely candidates. Expert commentary : To achieve eubiosis, manipulation of the gut microbiota must occur in some form. Several approaches for modulating gut microbiota include prebiotic diets, antimicrobial interventions, fecal microbiota transplants, and selective probiotics. One novel approach showing promising results is the use of selective bacterial candidates to modulate microbial composition. Use of single microbe for treatment has an advantage as compared to multi-species as microbes grow at different rates and if needed, a single microbe is easy to target.